Optimization of winding conditions for preventing roll defects caused by thermo-viscoelastic property and its experimental verification - Hiromu HASHIMOTO (The Japan Society of Mechanical Engineers, 2016)
Mainly produced on roll-to-roll systems, plastic films are used in various high functional products. During the final stage of the production, the films are continuously wound into a roll, which is then shipped to storage and transported; in some cases it is heat-treated at various temperatures. Over time, the in-roll stress of the roll will change as a result of thermal strain and the viscoelastic properties. These factors can generate roll defects such as slippage or wrinkling. Based on the optimum design technique, this paper describes an optimization method for wind-up tension that prevents roll defects caused by thermo-viscoelastic properties. Experimentation confirms the optimized tension and shows that the in-roll stress distributions are significantly improved, thus preventing both wrinkles and slippage.